A new genus of Cicadellini (Hemiptera: Cicadellidae) from the Oaxacan Cloud Forest, with taxonomic notes on allied red-striped genera - Pinedo-Escatel, Jorge Adilson; Blanco-Rodríguez, Edith (European Journal of Taxonomy, 2024)
Cicadellinae is a relatively large subfamily of leafhoppers (Hemiptera: Cicadellidae) with a cosmopolitan distribution with most genera known to occur in the Neotropics. Mexico houses nearly 16% of the total genera and most are endemic, inhabiting threatened native forests. Here, a new unusual Mexican genus, Christopherus gen. nov., is described to accommodate a new species of Cicadellini, C. mictlantecuhtli sp. nov., collected in the endangered Cloud Forest of Sierra Juárez, Oaxaca State of Mexico, based on dry-pinned museum specimen data. The new taxa can be separated from other Neotropical Cicadellini genera easily using male genitalia features: (i) pygofer without processes, (ii) segment 10th without processes, (iii) paraphysis absent, and (iv) edeagus with single basal atrial process elongate and asymmetrical. The monotypic genus Gillonella with its type species, G. ampulla Nielson & Godoy, 1995, are redescribed. A detailed extensive morphological description and discussion to distinguish the new genus from allied red-striped Neotropical genera in Mexico, Central America, and South America are given. Distributional data for new taxa within Mexican forests is also provided.